2013
DOI: 10.4100/jhse.2012.8.proc2.18
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physical activity level in office employees groups in Albania

Abstract: Bozo D, Pano G, Çitozi R. Assessment of physical activity level in office employees groups in Albania. J. Hum. Sport Exerc. Vol.8, No. Proc2, pp. S152-S164, 2013. Insufficient PA is very common in office employees and due to this they are at higher risk for metabolic, cardiovascular and many more other health related risk factor diseases. There is a lack of data regarding the PA level of office employees groups in Albania. Thus the aim of this paper was to identify the PA level in typical representative groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Levels of physical activity amongst the young and adults seem to have shown a steady decline in the last few decades in many countries (French, Story & Jeffery 2001 ; Reilly et al 2004 ). According to Bozo, Pano and Citozi ( 2013 ), office employees in Albania engaged in insufficient physical activity of <600 MET-minutes per week as reported by health professionals in many studies. Amongst the participants, women were found to be more physically inactive than men (Bozo et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of physical activity amongst the young and adults seem to have shown a steady decline in the last few decades in many countries (French, Story & Jeffery 2001 ; Reilly et al 2004 ). According to Bozo, Pano and Citozi ( 2013 ), office employees in Albania engaged in insufficient physical activity of <600 MET-minutes per week as reported by health professionals in many studies. Amongst the participants, women were found to be more physically inactive than men (Bozo et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Bozo, Pano and Citozi ( 2013 ), office employees in Albania engaged in insufficient physical activity of <600 MET-minutes per week as reported by health professionals in many studies. Amongst the participants, women were found to be more physically inactive than men (Bozo et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 29% of office workers, MPA was noted and HPA was reported in 11% participants in current study. 20 According to another study which was conducted on physicians using the same tool reported that 68.4% participants were on LPA category, 'MPA' was noted in 28.4% of the subjects and HPA was noted in only 3.2%. Males were reported more active in 'HPA' 4.3% and female 1.3%.…”
Section: Discussionmentioning
confidence: 98%
“…Sedentary behavior associated with the risk of obesity, having chronic diseases and premature deaths. Office workers who exposed to long period of workplace sitting that did not require high physical efforts workload were more likely to have NCDs than those who did not exposed (Biernat, Tomaszewski, & Milde, 2010;BOZO, Pano, & Çitozi, 2013;van Uffelen et al, 2010). Pan et al in 2009 reported that the factors influenced on physical inactivity can be classified into individual and environmental perspective (Pan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%